Targeting ferroptosis unveils a new era for traditional Chinese medicine: a scientific metrology study - Cao, Siyang; Wei, Yihao; Yue, Yaohang; Chen, Yingqi; Liao, Shuai; Li, Aikang; Liu, Peng; Xiong, Ao; Zeng, Hui (Frontiers in Pharmacology, 2024)
In the past eleven years, there has been a surge in studies exploring the regulatory effect of Traditional Chinese Medicine (TCM) on ferroptosis. However, a significant gap persists in comprehensive scientometric analysis and scientific mapping research, especially in tracking the evolution, primary contributors, and emerging research focal points. This study aims to comprehensively update the advancements in targeting ferroptosis with various TCMs during the previous 11 years. The data, covering the period from January 1, 2012, to November 30, 2023, were retrieved from the Web of Science database. For in-depth scientometric and visualized analyses, a series of advanced analytical instruments were employed. The findings highlight China's predominant role, accounting for 71.99% of total publications and significantly shaping research in this domain.Noteworthy productivity was observed at various institutions, including